2012
DOI: 10.21608/ejabf.2012.2111
|View full text |Cite
|
Sign up to set email alerts
|

Impact of some environmental factors on distribution of certain vector snails in five Egyptian Governorates

Abstract: The present study showed that the distribution of the intermediate host snails of Fasciola sp. and Schistosoma sp. varied among the five surveyed Egyptian governorates. It was found that the ratios of distribution of Lymnaea natalensis, Bulinus truncatus and Biomphalaria alexandrina snails of the total surveyed sites were 44.1%, 26.9% and 4.9% respectively. Moreover, infected L. natalensis, B. truncatus and B. alexandrina snails in these sites were 1.96%, 3.4% and 0.98% respectively. However, infected L. natal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…Njoku (2011) claimed that conductivity is a limiting factor to snail growth and abundance as snail population was high in medium with conductivity range 50-110 μmhos than in medium with lower ranges. These results are in line with that obtained by El-Kady et al (2000); Saad et al (2012) and Abdel-Wareth (2014).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Njoku (2011) claimed that conductivity is a limiting factor to snail growth and abundance as snail population was high in medium with conductivity range 50-110 μmhos than in medium with lower ranges. These results are in line with that obtained by El-Kady et al (2000); Saad et al (2012) and Abdel-Wareth (2014).…”
Section: Discussionsupporting
confidence: 93%
“…B. alexandrina, B. truncatus, L. natalensis, L. carinatus and C. bulimoides) was recorded in March and April (spring season) and in October and November (Autumn season) from irrigation and drainage canals in El-Ismailia governorate. Moreover, Kloos et al (2004);Owojori et al (2006); Ntonifor and Ajayi (2007);El-Khayat et al (2011); Saad et al (2012) and Abd El-Wakeil et al (2013) were supported these findings.…”
Section: Discussionmentioning
confidence: 83%
“…The snails can live in a wide range of mineral content in water till certain limiting [30]. On the contrary, it was found that the highest numbers of B. truncatus snails were found under low dissolved salts (100-300 ppm) while B. alexandrina snails were obtained from a range of 601-1000 ppm [31].…”
Section: Discussionmentioning
confidence: 99%
“…8). However, Saad et al (2012) indicated that B. alexandrina snails were found at wide TDS range of (601-1000 ppm). While, Goncalves et al (2017) indicated that Cu 2+ dissolution with inverse salinity dependence, the toxic effects observed for CuO NPs might be due to intrinsic toxicity mechanisms related to the nanoform and their aggregation plays a key role in their toxicity.…”
Section: Effect Of Some Environmental Factors On Molluscicidal Activimentioning
confidence: 97%